Pandangan Guru dan Orang Tua Tentang Keterkaitan Penggunaan Handphone dengan Keterlambatan Bicara Anak - Aulia Khairunnisa Putri; Dwi Undayasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The use of handphones in this age of digitalization is increasingly widespread, both as a means of entertainment and as a pretext for learning media. Many parents and teachers use the latest technology to be a tool to help parenting in everyday life. However, it is not uncommon that many still ignore the impact that will be felt by children due to excessive use of cellphones and away from supervision, especially in the aspect of language development. This study aims to explore more deeply the perspectives of parents and teachers regarding the relationship between cellphone use and early childhood speech delay. The research method taken this time is mixed method, namely with quantitative and qualitative descriptive approaches with data collection techniques using questionnaires distributed and interviews to several parents and teachers as research subjects. The results showed that most teachers and parents agreed on the impact of cell phone use on children's speech development. The results show that the strongest reason for speech delay is due to the lack of verbal stimulation from the surrounding environment which is now starting to be replaced by cellphones. With this research, it is hoped that it will become a reference for parents and teachers to be wiser in giving children the freedom to use cellphones and be more active in interacting directly so that children's language and social development is more optimal.